Analisis Risiko dan Pengendalian Bahaya pada Pekerjaan Online Leak Sealing (OLS) di PT PLN Nusantara Power Up Rembang dengan Menggunakan Metode JSA - Odik Duwi Saputro; Imam Hermanto (Journal of Science, Technology, and Innovation, 2025)
Online leak sealing (OLS) operations in power generation facilities are characterized by a high level of complexity and risk, as they are conducted on pressurized and high-temperature systems without shutting down the operating unit. Such conditions necessitate a systematic and context-sensitive risk analysis approach to effectively minimize the potential for occupational accidents. This study aims to analyze risks and hazard control in OLS activities at PT PLN Nusantara Power UP Rembang using the Job Safety Analysis (JSA) method. The research adopts an empirical design comprising a preliminary survey, direct field observations, worker-focused discussions, and a review of operational procedure documents. Each stage of the OLS process is decomposed into micro-level activities, followed by the identification of potential hazards, associated probabilities, and consequences to construct a comprehensive JSA matrix. The findings indicate that the sealing compound injection and leak testing stages exhibit the highest concentration of risk, predominantly associated with exposure to pressurized fluids, hazardous chemicals, and potential equipment failure. The contextualized application of JSA provides a more granular depiction of risk profiles and serves as a foundation for formulating hierarchical control measures, thereby contributing to the strengthening of occupational health and safety management in high-risk online maintenance activities.